Effects of Team-Teaching and Blended-Learning Instructional Strategies on Health Promotion Competencies of Student Nurses in Universities in Southwestern Nigeria (2016)
There are evidences of poor knowledge and low role expectation in health prevention and wellness promotion among Nigerian nurses. This has been attributed to wrong pedagogical knowledge. The nature and characteristics of health promotion expects that its teaching should be based on andragogical and dialogical learning models like team-teaching and blended-learning strategies. This study, determined the effects of team-teaching (TTM) and blended-learning (BLM) instructional strategies on the health promotion competencies (HPCs) of student nurses in universities in Southwestern Nigeria. The moderating effects of self-efficacy and emotional intelligence were also examined. Health promotion and ecological models provided the framework. The pretest-posttest control group quasi experimental design of 3x3x3 factorial matrix was adopted. Participants were three intact classes of 400 level student nurses from Obafemi Awolowo University, Ile-Ife (OAU), Ladoke Akintola University of Technology, Ogbomoso (LAUTECH) and University of Ibadan, Ibadan (UI). They were assigned to TTM (LAUTECH-68), BLM (OAU-45) and Conventional teaching method (CTM) (Control) (UI-19) groups while treatment lasted eight weeks. General Self-efficacy (r=0.76), Emotional Intelligence (r=0.89), Health Promotion Competence (r=0.89) scales and instructional guides were used for data collection. Data were analysed using descriptive statistics, Analysis of covariance and Scheffe post - hoc test at 0.05 level of significance. Participants were 85.0% female and 15.0% male with a mean age of 27±7 years. There was significant main effect of treatment on HPCs (F(2, 128)=32.35; ŋ2=.34) of the student nurses. Participants in BLM (=31.64) had the highest post-mean score of HPCs compared to those in TTM (=27.50) and CTM (=17.66). There were significant main effects of emotional intelligence (F(2, 128)=21.37; ŋ2=.25) and self-efficacy (F(2, 128)=21.98; ŋ2=.26) on HPCs of the student nurses. Participants with high emotional intelligence recorded the highest post treatment mean of 29.79 followed by those with moderate (=28.70) and low (=18.50). Participants with high self-efficacy recorded the highest mean of 32.17 followed by those with moderate (=26.83) and low (=13.81) levels respectively. There was no significant two-way interaction effect of treatment and emotional intelligence on HPCs. There were significant two-way interaction effects of treatment and self-efficacy (F(2, 122)=13.52; ŋ2=.18) and emotional intelligence and self-efficacy (F(1, 131)=3.82; ŋ2=.04) on HPCs whereby, participants with low self efficacy in TTM group were most favoured; The three-way interaction effect of treatment, emotional intelligence and self-efficacy on HPCs was not significant. Blended-learning and team-teaching instructional strategies enhanced the health promotion competencies of student nurses in universities in Southwestern Nigeria, though the former was more effective. There is therefore the need to adopt these instructional strategies in inculcating health promotion competencies in student nurses.